Drug-induced liver injury. Part II: Late complications and hepatotoxicity monitoring - Kozielewicz, Dorota M.; Stalke, Piotr (Clinical and Experimental Hepatology, 2025)
The picture of drug-induced liver injury (DILI) is polymorphic, with variable intensity of clinical symptoms and prognosis. Most cases of DILI are acute, although the incidence of chronic hepatopathy has been reported to range from 3.4% to 39.0% in the period 6-12 months after discontinuation of the drug. The long-term chronic consequences of DILI in terms of morbidity and mortality are unclear. The rare obstructive bile duct syndrome is associated with an unfavorable prognosis – a higher risk of chronic liver failure and the need for liver transplantation. Other long-term forms of hepatopathy following DILI include progressive liver fibrosis, autoimmune hepatitis, hepatic steatosis, secondary sclerosing cholangitis, vascular lesions, and liver tumors. Recently, immune checkpoint inhibitors, which can cause an autoimmune-like phenotype, have also been shown to cause sclerosing cholangitis with infiltration of cytotoxic T cells in the biliary tract.